Understanding the Benefit–Cost Relationship in Long-Standing Community-Based Participatory Research (CBPR) Partnerships: Findings From the Measurement Approaches to Partnership Success (MAPS) Study. (September 2022) - Lachance, Laurie; Coombe, Chris M.; Brush, Barbara L.; Lee, Shoou-Yih Daniel; Jensen, Megan; Taffe, Brianna; Bhardwaj, Prachi; Muhammad, Michael; Wilson-Powers, Eliza; Rowe, Zachary; Caldwell, Cleopatra H.; Israel, Barbara A.
As part of the Measurement Approaches to Partnership Success study, we investigated the relationship between benefits and costs of participation in long-standing community-based participatory research (CBPR) partnerships using social exchange theory as a theoretical framework. Three major findings were identified: (a) the concept of benefits and costs operating as a ratio, where individual benefits must outweigh costs for participation, applies to early stages of CBPR partnership formation; (b) as CBPR partnerships develop, the benefits and costs of participation include each other's needs and the needs of the group as a whole; and (c) there is a shift in the relationship of benefits and costs over time in long-standing CBPR partnerships, in which partners no longer think in terms of costs but rather investments that contribute to mutual benefits.